吸附剂对植物油中3-氯丙醇酯、缩水甘油酯 和多环芳烃脱除效果的研究Removal effect of adsorbent on 3-monochloropropane-1,2-diol esters, glycidyl esters and polycyclic aromatic hydrocarbons in vegetable oil - 迟华忠1，安骏2，吴祥骞1，赵盼盼1，陆奕1，杨涛2 CHI Huazhong1，AN Jun2，WU Xiangqian1，ZHAO Panpan1，LU Yi1,YANG Tao2 (Zhongguo youzhi)
为探究吸附法脱除植物油中3-氯丙醇酯(3-MCPDE)、缩水甘油酯(GEs)和多环芳烃（PAHs）的效果，以活性炭、活性白土和硅藻土为吸附剂，对植物油中的3-MCPDE、GEs和PAHs进行脱除。结果表明：在吸附剂添加量为0.1%(以油样质量计)时，活性炭、活性白土和硅藻土对玉米油中的GEs的脱除效果差异显著，脱除效果依次为活性白土>活性炭>硅藻土，但3种吸附剂对3-MCPDE的脱除率均低于10%；随着活性白土添加量的增加，其对玉米油中GEs和3-MCPDE的脱除率呈上升趋势，在活性白土添加量1%时，玉米油中GEs的脱除率达到100%，此时3-MCPD的脱除率为27.78%；活性白土对不同植物油中3-MCPDE和GEs的脱除能力存在差异；与活性白土相比，活性白土与活性炭复合使用对玉米油中PAHs的脱除效果更佳，PAH4脱除率最高可达81.57%。综上，不同吸附剂对植物油中有害物质呈现出不同的脱除能力，在实际应用中需选择合适的吸附剂。 To investigate the efficacy of adsorption in removing 3-monochloropropane-1,2-diol esters (3-MCPDE), glycidyl esters (GEs), and polycyclic aromatic hydrocarbons (PAHs) from vegetable oils, activated carbon, activated clay, and diatomaceous earth were employed as adsorbents to remove 3-MCPDE, GEs and PAHs from vegetable oil. The results showed that at a 0.1% adsorbent dosage(based on oil mass), there was a significant difference in the removal efficiency of GEs in corn oil by three adsorbents, with performance ranking as activated clay > activated carbon > diatomaceous earth. However, the removal rates for 3-MCPDE remained below 10% for all adsorbents. Increasing activated clay dosage, GEs and 3-MCPDE removal rates in corn oil increased, achieving complete elimination (100%) for GEs at 1% dosage while attaining 27.78% removal rate for 3-MCPDE. Notably, activated clay displayed variations in adsorption capacity for 3-MCPDE and GEs across different vegetable oils. Compared with activated clay, the combination of activated clay and activated carbon had a better removal effect on PAHs in corn oil, and achieved maximum removal rate of 81.57% for PAH4. In summary, different adsorbents present different adsorption and removal capabilities for harmful substances in vegetable oil, and suitable adsorbents need to be selected in practical applications.